Open Access and Open Assessment: The Future of Peer Reviewed Journals? Experiences with a New Journal in Economics - Olaf Siegert; Korinna Werner-Schwarz (UCSIA, 2009)
Open Access Journals have become more and more popular as a publishing model for academic scholars. There are already more than 3,500 of them listed in the Directory of Open Access Journals (DOAJ). To establish these journals as a relevant and trustful source for validated research results (and as an alternative to licensed publisher-based journals), peer review is a necessary requisite. The Internet offers new ways to organize the peer review process. It allows for example comments and ratings from readers of freely available papers and articles. So far only a few Journals use these Open Assessment methods. The presentation will showcase “Economics - The Open-Access, Open-Assessment E-Journal” as one prime example. “Economics”, as the name indicates, covers papers from all parts of Economic Research. These papers, if accepted, are first published as Discussion Papers and then, after a successful evalution both by invited referees and by registered readers, as Journal Articles. The peer review stands in the centre of the journal, as its main goal is to be recognized as one of the top journals in its field. Therefore the traditional peer review process is substantially supplemented by a "public" peer review process in which the community of active researchers from all over the world has a hand in the evaluation process. After registering with the journal they can share their views in two ways. Either by commenting on the Discussion Papers in review or by rating the final Journal Articles. Within one year of existence, almost 1,800 researchers have registered with the journal. They are based all over the world including wellknown institutions like the American ivy league universities, the World Bank or the London School of Economics (LSE). After a slow start more and more comments and reviews are added to new papers, with now about four comments per paper. Even if the Article rating is less used so far, the overall picture is quite optimistic: Researchers are taking the chance of Open Assessment in Academic Journals, especially, if a critical mass of peers are following the same path.
Keywords: 330; Economics; Communication; Higher education; Universities; Open Access; Zeitschrift; Publikationsanalyse; Wirtschaftswissenschaft